Back pain beliefs among physiotherapists are more positive after biopsychosocially orientated workshops - O'Sullivan, Keiran; O'Sullivan, Peter; O'Sullivan, L.; Dankaerts, Wim (IOS Press, 2012)
Background: Negative low back pain (LBP) beliefs have been associated with greater disability among patients with LBP. The LBP beliefs of health care professionals (HCPs) are associated with the LBP beliefs of their patients. Intensive (8-day) education improves both the LBP beliefs of HCPs, and their stated management of LBP. However, it is unclear if shorter (2–3 day) educational workshops can effectively change the LBP beliefs of HCPs. This study examined whether educational, biopsychosocial workshops improve the LBP beliefs of physiotherapists. In addition, the study aimed to identify which LBP beliefs are modified, which factors facilitate these changes, and to compare LBP beliefs between countries. Methods: 150 physiotherapists attending a LBP workshop in one of three countries (Ireland, England or Germany) participated. LBP beliefs were evaluated using the Back Beliefs Questionnaire (BBQ) before and after the workshops. A small sample (n = 12) of participating physiotherapists identified the key perceived mediators of change in their LBP beliefs, and this data were analysed using thematic analysis. Results: Significant differences in LBP beliefs existed between countries, both at baseline and follow-up. BBQ scores across all three countries were significantly increased (p < 0.001), after the workshop. Combining the scientific evidence with live patient presentations were identified as important mediators of changing LBP beliefs. Conclusions: Biopsychosocially-orientated educational workshops improved the LBP beliefs of physiotherapists. Future studies should examine if LBP management changes after such educational workshops